Levels of Participation in Decision Making as Correlates of Job Satisfaction and Morale of Teachers in Public Senior Secondary Schools in Delta State (Global Journal of Management and Business Research, 2017)
The study investigated levels of teachers#x2019; participation in decision-making as correlates of job satisfaction and morale in public senior secondary schools in Delta State. The target population of the study consisted of all public senior secondary schools in Delta State. A sample size of 976 teachers in 36 public senior secondary schools in Delta State were drawn using stratified random sampling technique. The study was a correlational research aimed at determining the relationship among levels of participation in decision-making, job satisfaction and morale of teachers. The researcher therefore, formulated three research questions and three null hypotheses to guide the study. A research instrument titled #x201C;Questionnaire on Levels of Participation in Decision-Making, Job Satisfaction and Morale of Teachers#x201D; (QLPDMJSMT) was designed by the researcher. The instrument was validated in its face and content value and found reliable at a reliable index of 0.87 using Cronbach Alpha technique.
Keywords: PDM-participation in decision making; job satisfaction; nigeria